2021
DOI: 10.1016/j.stemcr.2021.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of mitochondrial DNA variants fluctuation during reprogramming and neuronal differentiation of human iPSCs

Abstract: Summary The generation of inducible pluripotent stem cells (iPSCs) is a revolutionary technique allowing production of pluripotent patient-specific cell lines used for disease modeling, drug screening, and cell therapy. Integrity of nuclear DNA (nDNA) is mandatory to allow iPSCs utilization, while quality control of mitochondrial DNA (mtDNA) is rarely included in the iPSCs validation process. In this study, we performed mtDNA deep sequencing during the transition from parental fibroblasts to reprogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 62 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…A study in 146 hPSC lines derived from healthy individuals observed that 76.6% of the lines displayed altered mtDNA mutation levels when compared to their parental somatic cells, with a mutation rate of $8.62 3 10 À5 /bp (Wei et al, 2021). Similar changes have been observed in hPSCs obtained from patients carrying pathogenetic mtDNA mutations (Palombo et al, 2021). Monitoring mtDNA integrity should therefore be included in the characterization of newly generated hPSC lines (Table 1).…”
Section: How Should I Check the Genome Integrity Of Hpsc Lines After ...mentioning
confidence: 76%
See 1 more Smart Citation
“…A study in 146 hPSC lines derived from healthy individuals observed that 76.6% of the lines displayed altered mtDNA mutation levels when compared to their parental somatic cells, with a mutation rate of $8.62 3 10 À5 /bp (Wei et al, 2021). Similar changes have been observed in hPSCs obtained from patients carrying pathogenetic mtDNA mutations (Palombo et al, 2021). Monitoring mtDNA integrity should therefore be included in the characterization of newly generated hPSC lines (Table 1).…”
Section: How Should I Check the Genome Integrity Of Hpsc Lines After ...mentioning
confidence: 76%
“…The quantification of mtDNA changes can be performed by PCR, followed by Sanger sequencing, next-generation sequencing (NGS), or Nanopore sequencing. Primers for amplifying mtDNA molecules into two segments need to be located outside the regions involved in the generation of breakpoints underlying mtDNA deletions (Palombo et al, 2021). Alternatively, high-depth mtDNA sequences can be extracted from WGS (Wei et al, 2021).…”
Section: How Should I Check the Genome Integrity Of Hpsc Lines After ...mentioning
confidence: 99%
“…There has also been recent work studying the impact of mitochondrial heteroplasmy on iPSC differentiation potential. Several studies now suggest mtDNA integrity as mandatory iPSC selection criteria [86][87][88] . Heteroplasmy of several mutations have been linked to iPSC's ability to differentiate [87][88][89][90] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies now suggest mtDNA integrity as mandatory iPSC selection criteria [86][87][88] . Heteroplasmy of several mutations have been linked to iPSC's ability to differentiate [87][88][89][90] . Manipulating MT heteroplasmy through insertion of wild type mtDNA has been shown to revert diseased iPSC state and improve pluripotency 91 .…”
Section: Discussionmentioning
confidence: 99%
“…Harnessing this technology is not without its challenges, one of which is to understand why different clonal lineages derived from a single donor behave differently in different contexts. Recent studies [1][2][3][4][5][6][7] have now shown that iPSCs derived from somatic cells contain mitochondrial single-nucleotide variants (mtSNVs) that affect only a proportion of the total mitochondrial DNA (mtDNA) content (that is, they are heteroplasmic). Interestingly, the proportion of mutant mtDNA (heteroplasmy level or fraction) can differ markedly in the derived iPSC cell lines.…”
Section: Main Textmentioning
confidence: 99%